Pengaruh Pursed Lip Breathing Exercise Terhadap Penurunan Tingkat Sesak Napas Pada Penyakit Paru Obstruksi Kronik (Ppok) Di Balai Besar Kesehatan Paru Masyarakat BBKPM Surakarta - Bakti, Adhitya Kusuma; , Dwi Rosella K, S.St FT., M.Fis; , Sugiono S.Fis.MH.Kes (2015)
Chronic Obstructive Pulmonary Disease (COPD) is achroniclung disease characterized bylimitedairflowin the respiratory tractthat is not fully reversible. Shortness of breath occurs due to interference respiratory ventilation and a decrease in work function of muscles-the muscles of breathing. COPD cause varying degrees of disturbance include cough, chest pain, and shortness of breath, edema, changes inbreathing patterns, and changes in posture. The main factor of risk of COPD is cigarette smoke or smoke. Modalities of physic therapy can reduce interference from chest pain with exercise therapy in the form of breathing exercise. To improve ventilation and improve respiratory muscle work -respiratory muscle training is carried exercise. Pursed lip breathing therapy will reduce muscle spasm breathing, clear the airway, relieve respiratory tract. Based on the analysis of data on the effect of pursed lip Breathing Exercise to decreased levels of breathlessness using Wilcoxon test control group P=0.014, group P=0.002, indicating that the control and treatment groups equally - the same effect of reducing the level of asphyxiation but more good treatment group as more significant. While the results of the data analysis results obtained using the Mann Whitney Rank 12.60 Mean control group and the treatment group Mean Rank of 18.40 with a value P <0.043, which means there are different effect between the control group and the treatment group. The conclusions of this study are no influence of the control group and the treatment group to reduce shortness of breath but better treatment group.